Bamboo Resource and its Role in Ecological Security - Tripathi, Y. C.; Khawlhring, Lalnunsanga (Indian Forester, 2010)
Rapid and alarming deterioration in natural environment has become a matter of great concern for the entire globe. Exploding population, industrialization, man-made pollution, loss of forests, etc. are responsible for this disastrous ecological scenario. Carbon dioxide emissions are at historic highs and rising. Bamboo is emerged as a way out to effectively combat these problems. Development of bamboo resources and industries worldwide may promote economic and environmental growth, mitigate deforestation, prevent soil degradation, restore degraded lands and provide cleaner environment addressing the livelihood and poverty alleviation issues at the same time. The paper describes role of bamboo in controlling soil erosion, water conservation, land rehabilitation and carbon sequestration.